Performance Feedback and Firm Risk Taking: The Moderating Effects of CEO and Outside Director Stock Options - Lim, Elizabeth N. K.; McCann, Brian T. (Organization Science, 2014)
We contribute to the behavioral theory of the firm and the behavioral agency model by developing a theoretical framework that predicts the differential interaction effects of performance feedback and values of stock option grants of multiple agents on firm risk taking. We explain how chief executive officers (CEOs) versus outside directors awarded with stock option grants perceive negative or positive deviations from prior performance. We argue that in a negative attainment discrepancy context, high values of option grants will increase the risk aversion of CEOs who already bear excessive employment and compensation risks, resulting in less risk taking; however, it will enhance the risk-taking propensity of influential outside directors who increase monitoring and support for risky projects because their risk preferences are better aligned with those of shareholders. In a positive attainment discrepancy context, high values of option grants will amplify risk aversion in both CEOs and outside directors who perceive risky strategies as potential threats to anticipated incentive values associated with a gain domain, thereby reducing risk-taking activities. Analysis of panel data from 1992 to 2006 on the research and development spending of U.S. manufacturing firms based on Arellano–Bond dynamic panel regression reveals findings largely consistent with our predictions.